2021
DOI: 10.3390/ijerph18115555
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity during the First Lockdown of the COVID-19 Pandemic: Investigating the Reliance on Digital Technologies, Perceived Benefits, Barriers and the Impact of Affect

Abstract: The measures to fight the spread of the COVID-19 pandemic have been concentrated on inviting people to stay at home. This has reduced opportunities to exercise while also shedding some light on the importance of physical health. Based on an online survey, this paper investigated physical activity behaviours of a Belgians sample (n = 427) during the lockdown period between the end of May 2020 and the beginning of June 2020 and found that, during this period, the gap between sufficiently and insufficiently activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
2
7
0
1
Order By: Relevance
“…To our knowledge, this is the first study to investigate PA levels during the lockdown in a sample of participants with PD. Although these findings agree with Chambonnière et al, who found that active older French adults showed greater decrease in PA during the lockdown than their inactive peers [13] , it contradicts other trials of healthy populations, observing an increase in PA level among active individuals [ 7 , 8 ]. The different results obtained in the present study could suggest that populations with mobility impairments more strongly depend on PA-facilitating environments to be active.…”
Section: Dear Editorsupporting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, this is the first study to investigate PA levels during the lockdown in a sample of participants with PD. Although these findings agree with Chambonnière et al, who found that active older French adults showed greater decrease in PA during the lockdown than their inactive peers [13] , it contradicts other trials of healthy populations, observing an increase in PA level among active individuals [ 7 , 8 ]. The different results obtained in the present study could suggest that populations with mobility impairments more strongly depend on PA-facilitating environments to be active.…”
Section: Dear Editorsupporting
confidence: 80%
“…A review identified significant decreases in PA levels among adults worldwide due to the pandemic [6] . However, some authors called for nuance: according to their results, individuals who were physically active before the lockdown actually managed to increase their PA level during confinement [ 7 , 8 ]. Such findings were observed only among healthy individuals, and no study investigated whether this was also the case among individuals with PD.…”
Section: Dear Editormentioning
confidence: 99%
“…Martin and colleagues, however, report significant and large increases in the use of online workouts during the lockdown in recreational sport participants in the United Kingdom, with almost 83% of users during lockdown being non-users pre-lockdown [ 26 ]. Similarly, a Belgian study found a significant increase in the use of mediated support, including online videos and online sports classes, during the first lockdown compared to the time before the lockdown [ 27 ]. Watching online videos during the lockdown was one of the five predictors of being physically active, according to current guidelines in this report [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Belgian study found a significant increase in the use of mediated support, including online videos and online sports classes, during the first lockdown compared to the time before the lockdown [ 27 ]. Watching online videos during the lockdown was one of the five predictors of being physically active, according to current guidelines in this report [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 1,809 adults in the United States, the most common reason for increasing PA during the COVID-19 pandemic was more time, whereas the most common barriers for PA were motivation and worry/stress ( Knell et al, 2020 ). A survey of 427 adults in Belgium showed that worsened time allocation, experiencing PA as effortful, and lack of family encouragement were significant barriers to PA, whereas better time allocation and not experiencing PA as effortful predicted higher levels of PA ( Symons et al, 2021 ). Another survey of 1,521 adults in the United Kingdom showed that physical opportunity and reflective motivation were the most consistent predictors of PA behaviour, while automatic motivation was not or negatively associated with PA ( Spence et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%